2009
DOI: 10.1016/j.seppur.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on DDT degradation in aqueous solution using bimetallic Ni/Fe nanoparticles

Abstract: a b s t r a c tIn this study, bimetallic Ni/Fe nanoparticles were prepared and the ability of this material to degrade DDT in aqueous solution was investigated at room temperature. Besides comparing the degradation rates of DDT using monometallic zero-valent iron and bimetallic Ni/Fe, batch investigations with bimetallic Ni/Fe nanoparticles were conducted to explore the influence of pH value on the degradation rate of DDT in aqueous solution. Results indicate that weakly acidic (4 ≤ pH < 7) or alkaline reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(50 citation statements)
references
References 21 publications
(32 reference statements)
0
50
0
Order By: Relevance
“…Numerous studies demonstrated that DDT degradation splits into two ways: a dehydrochlorination pathway and a hydrodechlorination pathway (Zinovyeva et al, 2005;Piechochi et al, 2009;Tian et al, 2009a). In the initial stage of the reaction, the aliphatic moiety of DDT can be subjected to a dehydrochlorination to form DDE or to a hydrodechlorination to form DDD.…”
Section: Dechlorination Pathway Of Ddtmentioning
confidence: 99%
“…Numerous studies demonstrated that DDT degradation splits into two ways: a dehydrochlorination pathway and a hydrodechlorination pathway (Zinovyeva et al, 2005;Piechochi et al, 2009;Tian et al, 2009a). In the initial stage of the reaction, the aliphatic moiety of DDT can be subjected to a dehydrochlorination to form DDE or to a hydrodechlorination to form DDD.…”
Section: Dechlorination Pathway Of Ddtmentioning
confidence: 99%
“…Most published studies targeting 87 dechlorination of chlorinated organics have however used bimetallic nZVI, containing small 88 amounts of Palladium (Pd) or Nickel (Ni). These include organochlorine pesticides (Zhang, 2003), 89 polychlorinated biphenyls (PCBs), trichloroethylene (TCE) (Schrick et al, 2002), 90 pentachlorophenol (PCP) (Zhang and Elliott, 2006), atrazine (Zhang et al, 2011) and DDT 91 degradation in water (Tian et al, 2009). Even though bimetallic nZVI is effective for pollutant 92 degradation, it has drawbacks regarding cost efficiency and environmental compatibility due to 93 spreading of other metals than Fe (Mueller et al, 2012).…”
mentioning
confidence: 99%
“…Studies have aimed at enhancing utility efficiency of Fe 0 by introduction hydrogen donors in order to increase available H + concentration, such as inorganic and organic acid [9][10][11][12][13]. Meanwhile, addition of acid can also retard the formation of passivation layers on particles surface because the precipitates of iron oxide is dependent on the pH of water in terms of mechanisms depicted as follows [6,10,13].…”
Section: Introductionmentioning
confidence: 99%